Political Contingency : Studying the Unexpected, the Accidental, and the Unforeseen. - Shapiro, Ian (NYU Press, 2007)
History is replete with instances of what might, or might not, have been. By calling something contingent, at a minimum we are saying that it did not have to be as it is. Things could have been otherwise, and they would have been otherwise if something had happened differently. This collection of original essays examines the significance of contingency in the study of politics. That is, how to study unexpected, accidental, or unknowable political phenomena in a systematic fashion. Yitzhak Rabin is assassinated. Saddam Hussein invades Kuwait. Hurricane Katrina hits New Orleans. How might histor.